Mitigation of plasma-induced damage in porous low-k dielectrics by cryogenic precursor condensation. (1st April 2016) - Zhang, Liping; de Marneffe, Jean-François; Leroy, Floriane; Lefaucheux, Philippe; Tillocher, Thomas; Dussart, Remi; Maekawa, Kaoru; Yatsuda, Koichi; Dussarrat, Christian; Goodyear, Andy; Cooke, Mike; De Gendt, Stefan; et al.
Abstract: The present work describes the plasma etch properties of porous organo-silicate materials at cryogenic temperature. The mechanism of plasma damage is studied by means of in situ ellipsometry and post-etch material evaluation. Using conventional volatile reactants such as SF6, it is found that low plasma damage can be achieved below  −120 °C through two main channels: pore sidewall passivation by molecular SF6 and partial condensation of non-volatile etch by-products. The protection can be enhanced by means of gas phase precursors with low saturated vapor pressure. Using C4 F8, complete pore filling is achieved at  −110 °C and negligible plasma-induced damage is demonstrated on both blanket and patterned low- k films. The characteristics of the precursor condensation process are described and discussed in detail, establishing an optimal process window. It is shown that the condensation temperature can be raised by using precursors with even lower vapor pressure. The reported in situ densification through precursor condensation could enable damage-free plasma processing of mesoporous media.